TINJAUAN ATAS PENGELOLAAN PERSEDIAAN BAHAN BAKU PADA DIVISI KENDARAAN KHUSUS PT. PINDAD (PERSERO) KOTA BANDUNG - Sukanda, Rini Septiani; Dewi, Amelia Sinta (Jurnal Riset Akuntansi, 2018)
Raw Material Inventory management is a very important aspect for a company of commerce, industry, and manufacturing because it has considerable value and have an influence on the size of the operating costs. On the inventory management of raw materials that are running there are several issues that caused the lack of human resources issues, among others: if shortage of raw materials, the customer will be disappointed and if the excess raw materials then there are some burdens that must be on the responsibility of companies, among others, the cost of damage goods for too long in the store, inventory shrinkage cost of raw materials, etc. By doing this research, it is expected all of these problems can be overcome, so that helped PT. Pindad (Persero) Bandung in increasing the effectiveness of the work. To conduct this research, the writer uses descriptive method, is descriptive research method, which is a way of research to depict or describe clearly the object under study. Compaction collection techniques used were interviews, observarsi and library research. By doing research at PT. PINDAD can help the problems that arise and inventory management of raw materials to be faster without consuming a greater cost. Keywords: Raw Material Inventory Management